2019
DOI: 10.20961/jab.v18i2.225
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Accounting Students’ Perception of Accounting Ethics; An Empirical Study in Indonesia

Abstract: This paper proposes a perception of accounting students to overview ethical behaviour during their study in accounting school. The perception is measured by factors pertaining influence to accounting ethics. The variables including perception to cheating misconduct, earning management, environment and culture consideration. A controlling variable of gender and course took are also included in the model. A model of ethical perception is proposed to answer four hypotheses. The sample is accounting students in Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
2
5
0
2
Order By: Relevance
“…The apprehension of punishment or negative consequences associated with unethical behaviour may lead accounting professionals to adopt ethical attitudes in line with societal expectations and legal standards. This perspective is reinforced by the findings of Ufere et al [ 33 ] and Hermawan et al [ 18 ], underscoring the impact of external pressures on ethical decision-making in accounting.…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…The apprehension of punishment or negative consequences associated with unethical behaviour may lead accounting professionals to adopt ethical attitudes in line with societal expectations and legal standards. This perspective is reinforced by the findings of Ufere et al [ 33 ] and Hermawan et al [ 18 ], underscoring the impact of external pressures on ethical decision-making in accounting.…”
Section: Literature Reviewmentioning
confidence: 90%
“…However, some studies which align with the theoretical works of DiMaggio and Powell [ 8 ] have shown the potential influence of additional belief factors such as normative belief, coercive belief, mimetic belief and religiosity on the individual's attitude ([ 18 , 24 , 28 ]; Oboh, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research model includes factors: Working environment, personal ethics, and management style of the company are factors that affect the professional ethics of accountants. Hermawan & Kokthunarina (2019) explained to analyze factors related to ethical influence accountant. Ethical perceptions are intended to help research identify many factors that can influence students' perceptions, as they can affect their future attitudes and behavior in the workplace.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Desse modo, faz-se relevante entender a importância da ética, uma vez que essa é considerada um princípio moral ou condutas de valores tanto em aspecto individual quanto em contexto geral (ELDER; ARENS; BEASLEY, 2008). No contexto contábil, a ética é relevante para o exercício profissional, uma vez que as informações evidenciadas ao público devem retratar a realidade da empresa (HERMAWAN, 2016).…”
Section: Introductionunclassified